Superhydrophobic surfaces with a dual-layer micro- and nanoparticle coating for drag reduction. (15th April 2017) - Taghvaei, E.; Moosavi, A.; Nouri-Borujerdi, A.; Daeian, M.A.; Vafaeinejad, S.
Abstract: We propose a facile and cost effective method for fabricating superhydrophobic surfaces with significant drag reduction in a wide velocity range. A dual structure superhydrophobic aluminum surface with a hydrophobic Al2 O3 micro- and nanoparticle coating and also another superhydrophobic surface with a nanoparticle layer coating are fabricated. Then, the resulted drag from each of these surfaces is measured carefully in different velocities and compared with the drag of the as-received aluminum surface. Our results reveal that the surface with the dual structure experiences drag reduction in a wider velocity range compared with the nanoparticle coated sample. Drag reduction of the dual structure substrate is between 77 and 5% for Reynolds number of 4.7 × 10 4 and 2.35 × 10 5, respectively. The fabricated dual structure also shows a good durability which makes it favorable for many applications. Highlights: A superhydrophobic surface with dual micro/nano alumina particles is fabricated. The surface shows great drag reduction characteristic over wide Reynolds numbers. The surface shows great durability in water. Durability and drag reduction capability makes it suitable for marine applications. This surface can be used to cover inside of pipes in order to reduce pressure drop.